TATA KELOLA KEUANGAN PADA MADRASAH ALIAH BABUSALAM PAYARAMAN KABUPATEN OGAN ILIR - Basori, Ahmad; Widayatsih, Tri; Furkan, Nuril (Jurnal Manajemen Pendidikan, 2025)
The implementation of education at Madrasah Aliah Babussalam Payaraman requires financial support that is not small. In the aspect of meeting the financing needs or funds for the implementation of education at Madrasah Aliah Babussalam Payaraman is supported by three sources of funds, namely the South Sumatra provincial government and the central government and the community. In this study, the research method used is basic research, which is research to develop the theory of school financial governance by paying attention to the five principles of financial governance. This research discusses financial governance at Madrasah Aliah Babussalam Payaraman can be Financial management at Madrasah Aliah Babussalam Payaraman can be concluded in the good category. The results of this study are financial management at Madrasah Aliah Babussalam Payaraman has implemented four management functions, namely the management function, namely the planning function, the organizing function, the implementation function and the supervision function have applied the principles of transparency, efficiency, effectiveness, accountability and flexibility, and in accordance with the technical guidelines (juknis) for the use of government and community assistance funds.